Resistant Maltodextrin Intake Reduces Virulent Metabolites in the Gut Environment: A Randomized Control Study in a Japanese Cohort - Nishimoto, Yuichiro; Mizuguchi, Yoshinori; Mori, Yuka; Ito, Masaki; Miyazato, Shoko; Kishimoto, Yuka; Yamada, Takuji; Fukuda, Shinji (Frontiers in Microbiology, 2022)
In recent years, there have been many reports on the effects of prebiotics on intestinal health. In particular, consumption of resistant maltodextrin (RMD) has been reported to be beneficial. However, there has been no comprehensive quantification of the effect of RMD on the intestinal environment. Therefore, this study aimed to quantify the effects of RMD on the intestine, especially the intestinal microbiome and metabolome profiles. A randomized, double-blind controlled trial was conducted in 29 Japanese subjects with relatively high hemoglobin A1c (HbA1c) levels (Clinical trial no. UMIN000023970, https://upload.umin.ac.jp/cgi-open-bin/ctr_e/ctr_view.cgi?recptno=R000027589). The subjects consumed RMD or placebo twice per day for 24 weeks. Blood and fecal samples were collected before and after the intake. The intestinal environment was assessed by a metabologenomics approach involving 16S rRNA gene-based microbiome analysis and mass spectrometry-based metabolome analysis. The intake of RMD increased the levels of Bifidobacterium and Fusicatenibacter, and decreased deoxycholate levels. Additionally, intake of RMD lowered the levels of some virulent metabolites, such as imidazole propionate and trimethylamine, in subjects with an initially high amount of those metabolites. RMD may have beneficial effects on the gut environment, such as commensal microbiota modulation and reduction of virulence metabolites, which is known as a causative factor in metabolic disorders. However, the effects of RMD partially depend on the gut environmental baseline.